1996
DOI: 10.1021/bi9600456
|View full text |Cite
|
Sign up to set email alerts
|

D38 Is an Essential Part of the Proton Translocation Pathway in Bacteriorhodopsin

Abstract: At present, almost no knowledge exists about the functional relevance of the amino acid residues at the cytoplasmic (CP) surface of the light-driven proton pump bacteriorhodopsin (BR) although a prerequisite for efficient vectorial proton translocation is the efficient capture of protons from the alkaline cytoplasm of the cell. To identify residues involved in the proton transfer reaction steps in the CP part of BR, the aspartic and glutamic amino acids D36, D38, D102, D104, and E161 were replaced by cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 51 publications
9
98
0
Order By: Relevance
“…Furthermore, we showed recently that incorporation of CytcO into a membrane results in acceleration of the protonation rate of a surface-exposed pH-sensitive fluorescent dye at the n side of the membrane (49). Also data from earlier studies show that proton migration along proteinmembrane surfaces may be faster than proton exchange between surface residues and the bulk solution (50), which involves specific surface residues (51,52).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, we showed recently that incorporation of CytcO into a membrane results in acceleration of the protonation rate of a surface-exposed pH-sensitive fluorescent dye at the n side of the membrane (49). Also data from earlier studies show that proton migration along proteinmembrane surfaces may be faster than proton exchange between surface residues and the bulk solution (50), which involves specific surface residues (51,52).…”
Section: Discussionmentioning
confidence: 94%
“…On the "macroscopic" level, the ability of surface buffers to retard the propagation of a proton pulse was addressed both experimentally [32,33] and theoretically [30,31,34,35]. On the "microscopic" level, it has been shown that the replacement of particu lar amino acid residues at the n surface of BR membranes affected the enzyme kinetics [36]. These data indicated the contribution of the surface exposed amino acids in the efficient collection/trapping of protons (further evidence of such involvement can be found in review [37]).…”
Section: Interfacial Potential Barrier: Propertiesmentioning
confidence: 99%
“…Studies on some specific membrane-bound proton pumps, for example cytochrome c oxidase or bacteriorhodopsin (9)(10)(11)(12), have revealed higher than diffusion-limited rates of proton uptake (9,(13)(14)(15). It has been hypothesized that these proteins have a surface proton-collecting antenna, consisting of negative and buffering groups, aiding the proton uptake (12,16,17). Theoretical studies also indicate that the membrane itself can contribute to this proton uptake (18)(19)(20).…”
mentioning
confidence: 99%